Cibercultura, imaginário e juventude: a influência da internet no imaginário de jovens brasileiros - Ferreira, Lygia Socorro Sousa (2009)
The Master dissertation is inserted in the present planetary mediatic arrangement configured by the convergence between communication and the data processing information: cyber-culture. We are currently living in a time impacted by continuous scientific advancements and, moreover, by the huge utilization of info-technologic equipment. The interactivity and speed are now conceived as processes capable of dynamizing the socio-cultural, political and economic relations of the contemporary life. On that context, where interactive technologies became essential, it is important to investigate the Internet s influence on the Brazilian youngsters imaginary. Nowadays, the social relationships are built with the help of digital technologies and the cyberspace. The question arises, then: How does the Internet impact the youth? Do the relationships measured by the Web collaborate for the autonomy and identity formation of young people? How does the Internet seduce them? The contents explored at the Web help in the personal formation of those individuals? The answers for those questions show that when reaching the virtual world, youngsters develop a feeling of autonomy and identity. At the same time, that relationship young people-Internet provides dependence and loneliness in a context occasionally taken over by criticism absence. In addition to the bibliographic research on the studied object, the work involves empirical research, through a specialized consultation with 100 youngsters aging 14 to 17 years old, students of public and private schools of Belém and São Paulo. The data study was done through qualitative and quantitative systemization and the results were posted in elucidative graphic spreadsheets. The theoretical perspectives deployed for the argumentation basis include post-modernism (Lyotard, Harvey, Kumar and Jameson), French post-structuralism (Baudrillard), communication post-Frankfurt critique (Sfez), socio-dromological theory (Virilio), cyber-culture critical epistemology (Trivinho) and the imaginarium theories (Castoriadis and authors of the psychological area), among other less relevant sources. The (theoretical and empirical) results reflect as contextual scientific conclusions on the problematic seduction of that coupling between youth and cyberspace